A systematic review and evidence assessment of monogenic gene-disease relationships in human male infertility - Zhao, Qian; Peng, Huifang; Chen, Jiali; Zhang, Hui; Ma, Yujin; Jiang, Hongwei (Frontiers in Endocrinology, 2025)
BackgroundGenetic factors play a significant role in human male infertility, with about 4% of infertile men currently identified with genetic reasons, yet most (60–70%) still lack a definitive diagnosis and remain unexplained. Similar to other medical fields, the advent of next-generation sequencing (NGS) has resulted in the discovery of a growing array of genetic variations in infertility issues affecting both genders. With the rising count of newly discovered genes, precise diagnoses are now possible for cases of male infertility that were once considered idiopathic. Nonetheless, substantial proof supporting the gene-disease relationships (GDR) remains absent in numerous instances.Objective and rationaleThe year 2019 and 2021 saw the release and revision of the standardized clinical validity evaluation for monogenic reasons behind male infertility. In this report, we offer an extensive review to methodically assess all existing data (spanning from 1 Jan, 2020, to 24 Sep, 2024) regarding the singular causes of either isolated or syndromic male infertility, hormonal imbalances, or reproductive irregularities in male reproductive organs.Search methodThe PRISMA protocols were utilized to gather comprehensive data from PubMed and Web of Science regarding the genetics of human male infertility and disorders of sex development (DSD) resulting in infertility, spanning from 1 January 2020 to 24 September 2024. The pathologies examined encompass both isolated infertility and syndromic male infertility, along with disorders of the endocrine and reproductive systems. A standardized scoring system was used to evaluate whether pathogenic variations in a particular gene lead to a recognized phenotype. Each GDR received a conclusive rating, ranging from no evidence to definitive.OutcomesOut of 19885 identified and screened publications, 229 were chosen for gene and variant analysis. Our research has pinpointed 191 genes and confirmed 191 GDRs, encompassing all documented single-gene reasons for male infertility and DSD. Additionally, our research pinpointed 100 genes with at least a moderate connection to male infertility or atypical genitourinary development traits. The study did not take into account associated genetic risk factor(s) or oligogenic/polygenic causes of male infertility.Systematic review registrationhttp://www.crd.york.ac.uk/PROSPERO, identifier CRD42024593082.